A Case of Segmental Arterial Mediolysis Presenting as Mucosal Gastric Hematoma. (23rd November 2017) - Sakuraba, Shunsuke; Orita, Hajime; Ueda, Shuhei; Tokuda, Satoshi; Ito, Tomoaki; Kushida, Tomoyuki; Sakurada, Mutsumi; Maekawa, Hiroshi; Wada, Ryo; Sato, Koichi
Abstract : Background . Although segmental arterial mediolysis (SAM) has been increasingly recognized as arteriopathy and there are some case reports about SAM, it is still very rare. It is characterized clinically by aneurysm, dissection, stenosis, and occlusion within splanchnic arterial branches, causing intra-abdominal hemorrhage or bowel ischemia. Mortality is as high as 50% in acute events. Case Presentation . A 51-year-old man was referred to our hospital with hematemesis. Gastroscopy revealed a submucosal-like tumor on the posterior wall of gastric angle with ulceration. Computed tomography indicated a tumor measuring65 × 50  mm in the stomach, which was suspected to have invaded into the pancreas. Significant hematemesis recurred; the patient developed shock and underwent emergency distal gastrectomy, distal pancreatectomy, and splenectomy. The pathology and the clinical course were compatible with SAM splenic artery rupture causing retroperitoneal hemorrhage that penetrated into the stomach. After that surgery, aneurysm of common hepatic artery ruptured and coil embolization was performed. Conclusion . SAM is an important cause of intra-abdominal or retroperitoneal hemorrhage in patients without underlying disease. SAM typically presents as intra-abdominal hemorrhage, but, in this case, the retroperitoneal hemorrhage penetrated into the stomach and it looked like a submucosal tumor.